Optimasi Sediaan Toner Wajah Daun Pegagan (Centella Asiatica) Sebagai Anti Acne Dengan Variasi Polisorbat 20 Dan Gliserin Menggunakan Metode Simplex Lattice Design - Sabiti, Farroh Bintang; Juarti, Ika Buana; Alfa, Zahra Syani (Jurnal Farmasi & Sains Indonesia, 2024)
One common issue that arises from insufficient facial hygiene is acne. Treatment of acne using synthetic drugs, such as antibiotics and retinoids, is usually administered topically in the form of ointments. However, the use of these drugs often results in side effects such as skin irritation. Therefore, there is a need for herbal remedies that can address this issue, one of which is the use of gotu kola leaves. Gotu kola (Centella Asiatica) is a plant that has many benefits, with numerous studies indicating its impact on inhibiting the growth of bacteria that cause acne, such as S. aureus, Proteus vulgaris, and Escherichia coli. Hence, further research is needed to determine the optimal formula for a facial toner preparation containing gotu kola leaves (Centella Asiatica) as an alternative therapy for acne-prone skin, with variations of polysorbate 20 and glycerin.This study aims to determine the optimum formula for a facial toner preparation containing gotu kola leaves (Centella Asiatica) that meets the physical parameters of the preparation and to determine the optimal concentrations of polysorbate 20 and glycerin that can produce the optimum formula for the facial toner preparation containing gotu kola leaves (Centella Asiatica). This research employs laboratory experimental methods, and the results indicate that the optimum formula for the gotu kola leaf toner preparation (Centella Asiatica) has concentrations of Polysorbate 20 at 10% and Glycerin at 5%. Organoleptic testing, homogeneity testing, viscosity testing, and pH testing of the optimum formula meet the range of parameters and requirements for evaluating the physical properties of a good toner preparation.